The Electoral Misinformation Nexus: how news consumption, platform use, and trust in news influence belief in electoral misinformation - Mont’Alverne, C; Ross Arguedas, A; Banerjee, S; Toff, B; Fletcher, R; Nielsen, R (Oxford University Press, 2024)
Electoral misinformation, where citizens believe false or misleading claims about the electoral process and electoral institutions—sometimes actively and strategically spread by political actors—is a challenge to public confidence in elections specifically and democracy more broadly. In this article, we analyze a combination of 42 million clicks in links and apps from behavioral tracking data of 2,200 internet users and a four-wave panel survey to investigate how different kinds of online news and media use relates to beliefs in electoral misinformation during a contentious political period—the 2022 Brazilian presidential elections. We find that, controlling for other factors, using news from legacy news media is associated with belief in fewer claims of electoral misinformation over time. We find null or inconsistent effects for using digital-born news media and various digital platforms including Facebook and WhatsApp. Furthermore, we find that trust in news plays a significant role as a moderator. Belief in electoral misinformation, in turn, undermines trust in news. Overall, our findings document the important role of the news media as an institution in curbing electoral misinformation, even as they also underline the precarity of trust in news during contentious political periods.